Trade and welfare effects of new trade policy instruments - Yvonne Wolfmayr; Elisabeth Christen; Hendrik Mahlkow; Birgit Meyer; Michael Pfaffermayr (FIW - Research Centre International Economics, 2024)
Geoeconomic concepts are gaining importance in EU trade policy. In this context new trade policy instruments are designed to protect the internal market against unfair trade practices, coercive actions as well as to ensure sustainable supply chains and the protection of human rights. The study extensively overviews seven policy instruments: Anti-Coercion Instrument (ACI), Enforcement Regulation (ER), International Procurement Instrument (IPI), Carbon Border Adjustment Mechanism (CBAM), Corporate Sustainability Due Diligence (CSDD), Level Playing Field Provisions in the EU-UK Trade and Cooperation Agreement (LPF), and EU Regulation on Deforestation-Free Products (EUDR). Using gravity models and a quantitative general equilibrium trade model, the impact of the selected trade policy instruments on trade and welfare of the EU as well as Austria is estimated based on different scenarios. – – Geoökonomische Konzepte gewinnen in der Handelspolitik der EU an Bedeutung. In diesem Kontext werden neue handelspolitische Instrumente entwickelt, um den Binnenmarkt vor unfairen Handelspraktiken oder Zwangsmaßnahmen zu schützen und gleichzeitig nachhaltige Lieferketten sowie den Schutz der Menschenrechte zu gewährleisten. Im Rahmen der Studie werden sieben neue wirtschaftspolitische Instrumente der EU analysiert: das Anti-Zwangsmaßnahmen-Instrument (ACI), die aktualisierte Durchsetzungsverordnung (ER), das Instrument für das internationale Beschaffungswesen (IPI), die Bestimmungen über gleiche Wettbewerbsbedingungen im Handels- und Kooperationsabkommen zwischen der EU und dem Vereinigten Königreich (LPF), die Richtlinie über die Sorgfaltspflicht von Unternehmen im Bereich der Nachhaltigkeit (CSDD) sowie umweltrelevante Instrumente wie die Entwaldungsverordnung (EUDR) und der CO2-Grenzausgleichsmechanismus (CBAM). Unter Verwendung von Gravitationsmodellen und einem quantitativen allgemeinen Gleichgewichtsmodell wird der Einfluss der ausgewählten handelspolitischen Instrumente auf den Handel und die Wohlfahrt der EU sowie Österreichs in verschiedenen Szenarien geschätzt.
Keywords: F13; F14; F15; F18; F55; Q01; Q56; 330; Geoeconomic concepts; EU trade policy; internal market; unfair trade practices; coercive actions; sustainable supply chains; human rights; trade policy instruments; Anti-Coercion Instrument; International Procurement Instrument; Carbon Border Adjustment Mechanism; Foreign Subsidy Instrument; Corporate Sustainability Due Diligence; Level Playing Field Provisions; EU-UK Trade and Cooperation Agreement; Enforcement Regulation; Deforestation Initiative; gravity models; quantitative general equilibrium trade model; impact; trade; welfare; scenarios